2013
DOI: 10.1152/jn.00048.2013
|View full text |Cite
|
Sign up to set email alerts
|

Preserving axosomatic spiking features despite diverse dendritic morphology

Abstract: Hay E, Schürmann F, Markram H, Segev I. Preserving axosomatic spiking features despite diverse dendritic morphology. J Neurophysiol 109: 2972-2981, 2013. First published March 27, 2013 doi:10.1152/jn.00048.2013.-Throughout the nervous system, cells belonging to a certain electrical class (e-class)-sharing high similarity in firing response properties-may nevertheless have widely variable dendritic morphologies. To quantify the effect of this morphological variability on the firing of layer 5 thick-tufted pyra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 57 publications
8
66
0
Order By: Relevance
“…Therefore, the changes in the dendritic surface can strongly modulate the AP onset rapidness at AIS. This recent findings were also suggested or implied in some of the previous experimental and theoretical studies (Bekkers and Hauser 2007;Hay et al 2013;Mainen et al 1995). Although the contribution of dendritic load on the AP initiation and onset at AIS wasn't included in CAIS model, this study presents important findings that should be further studied.…”
Section: Discussionsupporting
confidence: 74%
“…Therefore, the changes in the dendritic surface can strongly modulate the AP onset rapidness at AIS. This recent findings were also suggested or implied in some of the previous experimental and theoretical studies (Bekkers and Hauser 2007;Hay et al 2013;Mainen et al 1995). Although the contribution of dendritic load on the AP initiation and onset at AIS wasn't included in CAIS model, this study presents important findings that should be further studied.…”
Section: Discussionsupporting
confidence: 74%
“…First, the initiation site is very close to the soma, as previously noted, and axonal diameter is small compared to the soma, especially if the conductance load of the dendritic tree is considered [36]. Thus, biophysical theory predicts that the soma is a current sink for the initiation site [11], i.e., that most Na current entering the AIS flows to the soma, producing a voltage gradient between the two sites.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found active sodium and potassium currents in presynaptic terminals [53][54][55][56][57][58]; therefore, terminations were assigned the biophysical properties of nodes of Ranvier [45,59]. The nodes and terminals had the same passive parameters as the initial segment, including a specific capacitance (Cm) of 1 µF/cm 2 and cell-type-specific passive membrane resistance (Rm), while the myelinated sections had an Rm of 1.125 MΩcm 2 [60] and Cm of 0.02 µF/cm 2 [60][61][62].…”
Section: Myelinated Axon Biophysicsmentioning
confidence: 99%